Harmful tax competition in the European Union : - Kiekebeld, Ben J. (Kluwer, 2004)
The increased mobility of capital has resulted in a sharp increase in tax competition in which governments seek to attract or retain economic activity by creating ever-favorable tax climates for business. The purpose of this work by Kiekebeld (scientific researcher, Foundation for European Fiscal Studies, Erasmus U. Rotterdam, the Netherlands) is to investigate how harmful tax competition is dealt with in the European Union and what the relation is between the political achievements of like the Code of Conduct and other countermeasures of individual member states on the one hand and EU law on the other.